Theoretical analysis of the behavior of steel frame infilled with masonry walls by the diagonal strut method - Grandi,Alba Bruna Cintra De (2021)
Abstract In the last decades, several studies have been developed regarding structures composed by frames infilled with masonry walls, proving the increase of lateral stiffness by the infill. In this work, an analysis was carried out, based on design codes which adopt the equivalent diagonal strut method, to compare theoretical results with experimental ones of tests performed on steel frames infilled with concrete block masonry. Two of the three assessed codes specify lateral stiffness smaller than that measured from experimental testing, as safety measures for design. Regarding the masonry ultimate loads, the two specifications analyzed yielded similar values of critical force, although they pointed out different failure modes. The equivalent diagonal strut method has been proved to be a simple and useful tool for considering masonry walls and it should be used in case of reduced horizontal loads, prior to initial cracks of the infill wall.